Decision Support System for Giving Annual Bonus at PT. Vizta Pratama by Using the Analytical Hierarchy Process (AHP) Method - Surya Ramadhan; Siswanto Siswanto; Jhoanne Fredricka (Jurnal Komputer, Informasi dan Teknologi, 2021)
PT Vizta Pratama Bengkulu is a branch of a franchise company engaged in family karaoke entertainment services, founded by a well-known dangdut singer, Inul Daratista and starting its first operation in 2005 in Kelapa Gading area. PT. Vizta Pratama Bengkulu has not used the Decision Support System Application. The decision to determine the recipient of the annual bonus is only to calculate the total value based on 3 criteria, namely responsibility, discipline, honesty without using a decision support method, therefore sometimes it is felt that the giving of employee annual bonuses is not right on target. Decision support system for giving annual bonus at PT. Vizta pratama using the analytical hierarchy process (AHP) method is a desktop-based application that has implemented the AHP (Analytical Hierarchy Process) method, this application runs on a Windows operating system created using the Visual Basic .NET programming language and SQL Server 2008r2. This application can be used to assist in the assessment process in determining the annual bonus at PT. Vizta Pratama Bengkulu where this application uses 4 predetermined criteria and then processed using the AHP (Analytical Hierarchy Process) method so as to produce values that will be ranked. Based on the results of the Blackbox testing that has been carried out, it can be concluded that the decision support system for providing annual bonuses at PT. Viztapratama by using the analytical hierarchy process (AHP) method is able to run well and can overcome data input errors by users and the SPK application with the Analytical Hierarchy Process method has provided effective results in accordance with the results of calculations using paired comparisons of 4 criteria where the comparison of pairs of criteria must produce consistent weighting criteria.